2022
DOI: 10.1177/10783903221079796
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Psychache and Suicide Risk With Spiritual Well-Being Levels of Patients Diagnosed With Depression

Abstract: BACKGROUND: Depression has long been accepted as a serious disability and burden globally, while suicide is a misunderstood and complex cause of death. Psychache is the psychological variable most strongly associated with suicidality. Spirituality is considered an important buffer against stressful events and may help people overcome distress and difficulties. AIMS: This study aims to determine how psychache and suicide risk are related to levels of spiritual well-being in patients with depression. METHODS: Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…In the current study, religious crisis was found to be a predictor of suicide risk. Meanwhile, in other studies on samples of healthy individuals, the strongest predictor of suicide risk was psychological pain (Campos et al, 2019;Surmacz et al, 2021;Tanrıverdi et al, 2022a). Contrary to the results of this study, spirituality was found to be a protective factor against suicide risk in other studies (Tae & Chae, 2021;Wu et al, 2015).…”
Section: H1contrasting
confidence: 99%
See 2 more Smart Citations
“…In the current study, religious crisis was found to be a predictor of suicide risk. Meanwhile, in other studies on samples of healthy individuals, the strongest predictor of suicide risk was psychological pain (Campos et al, 2019;Surmacz et al, 2021;Tanrıverdi et al, 2022a). Contrary to the results of this study, spirituality was found to be a protective factor against suicide risk in other studies (Tae & Chae, 2021;Wu et al, 2015).…”
Section: H1contrasting
confidence: 99%
“…A Polish study conducted during the Covid-19 pandemic on a population of healthy individuals found that psychological pain was the strongest predictor of suicide attempts (Surmacz et al, 2021). Similar results have been obtained in other populations (Campos et al, 2019;Tanrıverdi et al, 2022a). Shneidman (1998), after analysing suicide notes from people committing suicide, noted that most of them described 'intolerable' emotional distress and a belief that death was the only way to end it (Shneidman, 1998).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Mental pain in psychotic disorders has been the focus of several studies. It has been recognized as a risk factor for suicide, generalizable between different types of populations [13][14][15][43][44][45][46][47][48]. One such study, which involved 25 outpatients with schizophrenia and used Magnetic resonance imaging (MRI) data, found a correlation between high levels of psychological pain, increased suicidal risk, and altered cortical folding gyrification in the fronto-parietal region [14].…”
Section: Introductionmentioning
confidence: 99%